LOAD TRANSFER MECHANISM ON LOAD TRANSFER PLATFORM FOR SOFT SOIL REINFORCEMENT WITH RIGID INCLUSION IN PADANG-SICINCIN TOLL PROJECT - Afandi, Rizzal
Road structure planning on problematic soils needs concerning of geotechnical hazards to avoid potential failures both during construction and during operational periods. In road embankments on compressible soils, such as silt of clay and organic soils with a very soft to soft consistency, treatment with repair or strengthening of subgrade must be designed to avoid problems of failure of bearing capacity and or excessive embankment settlement. One of the methods is the installation of Rigid Inclusion which is intended to transfer the embankment load to the competent layer under compressible soil. This study aims to evaluate arching effects on the Loading Transfer Platform (LTP), investigate stress and strain on geosynthetics, and forces acting on the LTP layer with analytical calculation methods, numerical modeling using the PLAXIS 2D program based on the geotechnical instrumentation. The results of axisymmetric numerical modeling and readings of the Earth Pressure Cell (EPC) instrumentation show the contours of the arching effect in the LTP layer. The evaluation of tensile force of the geosynthetic in the LTP is 2.78 kN from the Vibrating Wire Strain Gauge (VWSG) instrumentation, 0.875 kN/m from the PLAXIS 2D analysis, is 9.45 kN/m from the analytical calculation with the Catenary method and 9.47 kN/m with the Parabolic method. The four analyzes showed quite varied values, where the PLAXIS 2D analysis results tending to be smaller and analytical calculation results tending to be larger (conservative) when compared to the instrumentation results. The results of vertical stress analysis on the LTP layer show that the smallest to highest result are field instrumentation readings (EPC and Fiber Optic), PLAXIS 2D analysis, and analytical calculation results. The analysis using PLAXIS 2D resulted in the efficient design that closed to the actual conditions that occur in the field.